2017
DOI: 10.1038/s41598-017-01662-y
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Controls on the Spatio-Temporal Heterogeneity of Deep Moisture in the Unsaturated Zone: A Hydrogeophysical Evaluation

Abstract: Information on the spatio-temporal variability of soil moisture in the vadose zone is important to assess groundwater recharge and solute transport in unconsolidated substrate as influenced by biological processes. Time-lapse electrical resistivity imaging (ERI) was used to monitor soil moisture dynamics to a depth of 9 m in a grassland, a grassland encroached by a juniper species (eastern redcedar, Juniperus virginiana), a juniper woodland and an oak forest in the south-central Great Plains, Oklahoma, USA. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…Jobbagy and Jackson [51] reported that a Eucalyptus plantation reduced groundwater recharge, and decreased water table by 38 cm compared to adjacent grassland during a two-year period in the Argentine Pampas. Acharya et al [30] monitored water levels of perched aquifers under grassland and grassland encroached by Juniperus virginiana (Eastern redcedar) in the South-Central Great Plains, USA. They found that water level was higher under grassland than under Eastern redcedar woodland; this observation indicates that woody plants are likely to decrease water table in a perched aquifer.…”
Section: Water Table Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jobbagy and Jackson [51] reported that a Eucalyptus plantation reduced groundwater recharge, and decreased water table by 38 cm compared to adjacent grassland during a two-year period in the Argentine Pampas. Acharya et al [30] monitored water levels of perched aquifers under grassland and grassland encroached by Juniperus virginiana (Eastern redcedar) in the South-Central Great Plains, USA. They found that water level was higher under grassland than under Eastern redcedar woodland; this observation indicates that woody plants are likely to decrease water table in a perched aquifer.…”
Section: Water Table Methodsmentioning
confidence: 99%
“…Geophysical methods are increasingly used to understand catchment hydrology and evaluate vegetation impacts on groundwater recharge [30,[86][87][88]. Some geophysical methods include electrical resistivity imaging, electromagnetic induction, ground penetrating radar, and vertical electrical soundings.…”
Section: Geophysical Imagingmentioning
confidence: 99%
“…In addition to the effects of global warming, loss in vegetation cover in some regions produces changes that affect the partition of energy and water fluxes at the surface. Such alterations affect the capacity to assimilate atmospheric CO 2 and the capacity to intercept and store moisture in land surface reservoirs, leading to decreases in availability of water for human and ecosystem uses (Acharya, Halihan, Zou, & Will, ; Ghannam et al, ; Kim & Jackson, ; McColl et al, ; Winter, Harvey, Franke, & Alley, ). This phenomenon can be particularly dramatic in tropical ecosystems and has been documented to occur in a variety of locations worldwide (Allen et al, ; Chazdon, Brenes, & Alvarado, ; Condit, Hubbell, & Foster, ; Khan, Rodgers, Johnsingh, & Mathur, ; Laurance et al, ; Leigh, Windsor, Rand, & Foster, ; Lwanga, ; Phillips et al, ; Rolim, Jesus, Nascimento, do Couto, & Chambers, ; Williamson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This results in either a delayed or lack of response of soil moisture in deep soils to a precipitation pulse and reduces the deep recharge potential. Reduced coherence between the precipitation pulse and deep soil moisture for the redcedar woodland during pluvial condition suggests that the vegetation transition from herbaceous cover to woodland in the subhumid rangeland of the southern Great Plains will likely reduce the localized recharge of groundwater despite the increase of infiltration capacity and the potential decrease of overland flow in the redcedar woodland system [38,39].…”
Section: Drought Reduces the Coherence Of Subsoil Soil Moisture To Prmentioning
confidence: 99%